Active tectonics around the Cusco city, Peru: record of earthquakes in the last 14,000 years, from paleosismological data - Rosell Guevara, Lorena Nicole (2021)
The seismic activity of Peru has its origin in the convergent margin, where the Nazca plate subducts under the South American plate, a process that generates friction and accumulation of stress, reflected in deformation of the crust and superficial earthquakes (<30km of depth). Cusco was affected by earthquakes in 1950, 1650 and recently in 1986, the first two, major earthquakes of magnitudes greater than 7 MM (Silgado,1978). The Tambomachay active geological fault is located four kilometers to the north of the city of Cusco, and belongs to a large and wide deformation zone, where the structures have NWSE and E-W trends, known as the Zurite-Cusco- Urcos-Sicuani Fault System (Benavente et al., 2013). Recent studies show clear morphological and structural evidence of Quaternary activity on these structures (Sébrier et al., 1985; Mercier et al., 1992; Cabrera, 1988; Benavente et al, 2013), so they should be classified as an important seismogenic source; however, there has not been complete characterization to assess the seismic hazard to the city of Cusco, which currently houses over ~500,000 inhabitants. In this research investigation, we present a paleoseismological study of the western sector of the Tambomachay Fault. We present displacement rates, recurrence intervals and ages of recent seismic events